Five-year girl with advanced lupus nephritis and insulin dependent diabetes mellitus - V., Kishore S.; Barman, Sucheta; Pradhan, Subal Kumar (International Journal of Contemporary Pediatrics, 2020)
Systemic Lupus Erythematosus (SLE) and Insulin Dependent Diabetes Mellitus (IDDM) are two common auto immune disorder occurring in children which can involve the renal system. The condition when occurs simultaneously in a child and its effects and follow up on the kidneys and its management have been mentioned here. A five-year-old girl was presented with low grade fever, dryness of mouth and bilateral pain over knee joints over four months. She had facial puffiness, mild bilateral pedal edema, and ascites on admission. She was treated immunosuppressive medications following a renal biopsy and insulin for IDDM